Development of a new ternary blended cementitious binder produced from waste materials for use in soft soil stabilisation. (20th January 2018) - Jafer, Hassnen M.; Atherton, William; Sadique, Monower; Ruddock, Felicite; Loffill, Edward
Abstract: Soil stabilisation using traditional binders such as Ordinary Portland Cement (OPC), has a serious negative environmental impact, specifically carbon dioxide (CO2 ) emissions as a result of the manufacture of OPC. Because of this, the use of sustainable binders has become a critical issue to help reduce cement production through the use of by-product materials. This research seeks to develop a new ternary blended cementitious binder (TBCB) to replace cement for soft soil stabilisation. Different ternary mixtures containing wastes i.e., high calcium fly ash (HCFA), palm oil fuel ash (POFA) and rice husk ash (RHA) along with flue gas desulphurisation (FGD) gypsum used as a sulphate activator and grinding agent, were examined. The results illustrate that ternary mixtures improved the engineering and mechanical properties of stabilised soil. The results indicated that the plasticity index (PI) was reduced from 20.2 to 13.0 and the unconfined compressive strength (UCS) increased after 28 days of curing from 202 kPa to 944 kPa using the optimum non-FGD activated mixture. FGD contributed significantly by increasing the UCS to 1464 kPa at 180 days of curing, which surpassed that for the reference cement (1450 kPa), and by improving the soil consistency limits; where the PI decreased to 11.7 using TBCB compared with 14.5 for the soil treated with the reference cement. X-ray diffraction (XRD) and scanning electron microscopy (SEM) analysis revealed substantial changes in the diffraction patterns and microstructure components of the TBCB paste over the curing period, confirming the formation of cementitious products. A solid, coherent and compacted structure was achieved after treatment with TBCB as evidenced by the formation of C-S-H, CH and ettringite. Highlights: A symbiotic balance of the free lime and silica oxides has been proposed. A cement-free binder has been developed for soft soil stabilisation. FGD gypsum extensively contributed to the compressive strength evolution. UCS evolution was evidenced via the use of XRD and SEM techniques.